2015
DOI: 10.4103/1305-7456.163223
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of stress distributions in peri-implant and periodontal bone tissues in 3- and 5-unit tooth and implant-supported fixed zirconia restorations by finite elements analysis

Abstract: Objective:In this study, it is aimed to compare the distribution of stress on periodontal and peri-implant bone tissues in 3- and 5-unit-dental and implant-supported zirconia restorations using finite element analysis.Materials and Methods:Stress distribution formed in periodontal and peri-implant bone tissues as a result of chewing forces was analyzed in dental and implant-supported three-dimensional (3D) finite element models of zirconia restoration with 5-unit placed on the numbers of 43, 44, 45, 46, and 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…In general, the highest concentration of maximum principal stress was observed at the neck region of all the implants during their insertion. In a study done by Guven et al, stress distribution was evaluated in periodontal and peri-implant bone tissues in 3-and 5-unit-dental and implant-supported zirconia restorations using FEA, wherein it was concluded that maximum principal stress was observed at the premolar and molar region for the implant-supported prosthetic model [26]. Türker et al did the finite element stress analysis of applied forces to implants and supporting tissues using the all-on-four concept with different occlusal schemes and concluded that the highest stress on the implant was concentrated at the posterior region of the mandible when compared to the anterior region [27].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the highest concentration of maximum principal stress was observed at the neck region of all the implants during their insertion. In a study done by Guven et al, stress distribution was evaluated in periodontal and peri-implant bone tissues in 3-and 5-unit-dental and implant-supported zirconia restorations using FEA, wherein it was concluded that maximum principal stress was observed at the premolar and molar region for the implant-supported prosthetic model [26]. Türker et al did the finite element stress analysis of applied forces to implants and supporting tissues using the all-on-four concept with different occlusal schemes and concluded that the highest stress on the implant was concentrated at the posterior region of the mandible when compared to the anterior region [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different preferential alignment was seen in the Dentate and 12M groups in the infraorbital canal and nasal cavity oors. Sedat et al reported that stress accumulation in bone tissue in a tooth-supported model was less than in an implant-supported model 30) . It can be presumed that the difference in mechanical property between periodontal and peri-implant tissues may explain the stress accumulation reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 30 ] Some authors believe that increasing the number of implants can reduce the stresses on the supporting implants. [ 4 31 ] However, some authors believe that in the triangular arches adding the middle implant may be served as an indirect retainer or as a vertical stop for preventing sitting of the anterior portion of overdenture. [ 32 ] A study by Liu et al .…”
Section: Discussionmentioning
confidence: 99%